An Attempt to a New Interpretation of Bedros Tourian’s “Complaints” - AVAGYAN, VACHAGAN (Bulletin of Yerevan University B: Philology, 2021)
By detailed content and psychological analysis of the first lines of Bedros Tourian’s well-known poem “Complaints,” the article reveals the great importance of those lines for the poem’s further inner development and highly outlines the direction and nature of its spiritual content.
Keywords: Hrant Tamrazyan, Albert Sharuryan, Arshak Chobanyan, God, sun, farewell, tragedy, despair, damnation, worldview, allegory